MAKNA RAGAM HIAS SARUNG TENUN SUTERA MANDAR - Amri - (Pascasarjana Institut Seni Indonesia Surakarta, 2012)
This article summarized from the research report aimed at finding out the development of the ornament form of woven silk sarong of Mandar and its symbolic meanings. The method used was a descriptive qualitative one. The data was collected through observation, interviews and literature. Safri Sairin’s theory was used to study the development of the form of the ornament and Bagus Gede Triguna’s was used to study the symbolic meanings. The research results showed that the development of the ornament form of the woven silk sarong of Mandar had something to do with socio cultural changes, the economical level of the society, and the creativity of the weaver. The ornament in rectangle form in the society of Polewali Mandar symbolizes nature, glorious values of human characteristics and the concept of self-control. Keywords: woven cloth, silk sarong of Mandar, and development.